Procedural modelling techniques to configure driving serious game scenes - Pedro Miguel Cesário Rosa (2015)
This dissertation has the objective of tackling the road safety problem in order to further prevent accidents and casualties for both drivers and pedestrians by creating a tool that is capable of loading real world data from user selected locations and render them in 3 dimensional models for further use in serious driving games. These models are then populated with pedestrians that walk around and the ability to drive a vehicle is given to the user. Also the tool should be flexible enough to allow the users to configure the different conditions such as weather, time of day, rendering options, vehicle damage and pedestrian density, in order to conduct studies on different conditions. The project should also be open source, so anyone can edit it and expand it their own way to suit their needs and conduct specific studies. It features Oculus Rift integration, which further extends the possibility of conducting studies to the human driver by giving the possibility to expand this integration to evaluate the driver's behaviours. Another important aspect is the possibility to export the entire procedurally generated scene to a 3D file format that can be edited by an external application.By providing such tool for free, not only marks the beginning of an open source world 3D generator, but also a framework capable of allowing multiple different usages, such as conducting studies, building video game scenarios or be used as a learning tool by a driving school for instance. Hopefully this will increase road safety if used carefully as a serious tool.To do so we'll use the game engine Unity 5 to develop the project, CGIAR-CSI to download elevation data, Google Static Maps for the satellite imagery, OpenStreetMap for the location data and everything else is built inside Unity. Also UnitySlippyMap, which is a world map that works with various tile providers was used and integrated on the context of this project to allow users to select a location inside Unity.Along this document you will find a literature review on the topic, including related work and attempts to do similar projects followed by a comparison between other project and this one. The reader will also find details about development and the system's architecture as well as deep details about implementation. On the end you can find a few screen shots of the results of this project.Key Words: Procedural Modelling, Driving Simulation, World Locations, Serious Games, Road Safety